Ecological effects of antibiotics on aquatic microbial communities: Structure-function response dynamics and multifactorial drivers - Hu, Yening; Gai, Nan; Yuan, Zhimin; Zhou, Beihai; Hou, Rongrong; Yuan, Rongfang; Chen, Huilun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Antibiotics profoundly impact aquatic microbial communities, though their ecological effects remain incompletely understood. This review adopts a “structure–function coupling” perspective to analyze microbial response dynamics and driving mechanisms. Structurally, antibiotics significantly alter community composition and diversity by inhibiting sensitive taxa (e.g., Actinobacteria) and enriching resistant groups (e.g., Proteobacteria). Functionally, antibiotics inhibit key functional taxa, such as cyanobacteria and ammonia-oxidizing bacteria (AOB), thereby impairing energy metabolism and nutrient cycling processes. However, communities can enhance resilience by upregulating mechanisms such as reinforced carbon metabolism and DNA repair. This article first reveals the bidirectional feedback mechanism between structural and functional changes: for instance, the replacement of sensitive AOB by resistant AOB helps maintain nitrification function, while upregulation of efflux pump genes (e.g., ABC transporters) boosts resistant bacteria's competitiveness. These responses are regulated by multiple factors, with the type and concentration of antibiotics being particularly critical. Through integrated analysis, this study explains contradictory findings in the existing literature. Different antibiotics exhibit distinct ecological effects—for example, Bacteroidetes increase under erythromycin (ERY) but decrease under levofloxacin (LEV) exposure. Dose-dependent responses are also observed: low concentrations (ng/L–μg/L) may temporarily increase diversity and enhance metabolic function, while chronic exposure promotes adaptation. High concentrations (mg/L) often cause irreversible inhibition, such as reduced diversity and functional simplification. Additionally, environmental factors (e.g., nutrient levels, pH, dissolved organic matter, and co-occurring pollutants) and microbial interactions can indirectly mitigate or exacerbate these effects, complicating the determination of impact thresholds. [Display omitted] •First systematic review of antibiotics' effects on microbial physiological functions.•Structural change alters function; function adapts to support community reassembly.•Antibiotic type and concentration dictate response direction and intensity.•Dose-dependent response: low-dose stimulates, high-dose inhibits.•Standardized testing methods needed for low-dose chronic exposure thresholds.